The Grants, Concessions, and Original Constitutions of the Province of New-Jersey 78 (1752) - (:unkn) unknown (My University, 1668)
every Male from 16 Years and upwards, to the Age of 60 Years, shall be furnished at their own Cost and Charge, with good and sufficient Arms, and constantly maintain the same, viz., a good serviceable Gun well fixed, one pound of good Powder, four Pounds of Pistol Bullets, or Twenty four Bullets suited to the Gun, a Pair of Bandeleers, or a good Horn and a Sword and Belt...
Keywords: REQUIRED POSSESSION